An observational study of the impact of an antenatal asthma management service on asthma control during pregnancy. (February 2016) - Grzeskowiak, L.E.; Smith, B.; Roy, A.; Dekker, G.A.; Clifton, V.L.
Abstract: Objective: We sought to investigate the impact of introducing an antenatal asthma management service (AMS) on asthma control during pregnancy and subsequent perinatal outcomes. Study design: Prospective, observational cohort study of pregnant asthmatic women attending a tertiary hospital antenatal clinic. Asthmatic women were recruited from the antenatal clinic and were followed prospectively with visits at 12, 20, 28 and 36 weeks gestation. A new nurse-led AMS was introduced offering asthma self-management education and support. Outcomes were compared between women recruited before and after the AMS was introduced ( n  = 89 and 80, respectively) and included; prevalence of exacerbations during pregnancy, asthma control throughout pregnancy and perinatal outcomes, including preterm birth and small-for-gestational-age (SGA). Results: The relative risk for exacerbations (0.69; CI: 0.33–1.42), loss of control (0.67; CI 0.46–0.99) and persistent uncontrolled asthma (0.48; CI 0.26–0.9) were all reduced with attendance to AMS during pregnancy. AMS was associated with non-statistically significant reductions in asthma exacerbations (19.1–15.0%; p  = 0.480) and uncontrolled asthma at ≥2 study visits (21.3–11.3%; p  = 0.078). Conclusions: These findings demonstrate the potential impact of an AMS in improving asthma control during pregnancy, supporting the need for an adequately powered RCT to determine its clinical- and cost-effectiveness.